2004
DOI: 10.1097/00006231-200412000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peroxisome proliferator-activated receptor γ agonist, rosiglitazone, on dedifferentiated thyroid cancers

Abstract: Treatment with rosiglitazone increased the production of thyroglobulin in some patients with thyroid cancers, but only rarely restored scintigraphically significant iodine trapping. It remains to be shown whether longer treatment periods might result in a more efficient redifferentiating effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Activation of PPARg isoforms elicits both anti-neoplastic (Grommes et al 2004, Garcia-Bates et al 2008) and anti-inflammatory effects (Antonelli et al 2006) in several types of mammalian cells. Recently, it has been shown that agonists of PPARg induce apoptosis and exert antiproliferative effects on human papillary carcinoma cells (Ohta et al 2001), prevent distant metastasis of BHP18-21 tumors in nude mice in vivo (Ohta et al 2001), and induce redifferentiation in thyroid cancer cell lines (Klopper et al 2004, Philips et al 2004, Frohlich et al 2005, Park et al 2005, Aiello et al 2006, demonstrating effective therapeutic agents for the treatment of patients with thyroid cancer that fail to respond to traditional treatments (Klopper et al 2004, Philips et al 2004, Frohlich et al 2005, Park et al 2005. Moreover, the expression of PPARg gene and protein were examined in five human anaplastic cancer cell lines (Hayashi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PPARg isoforms elicits both anti-neoplastic (Grommes et al 2004, Garcia-Bates et al 2008) and anti-inflammatory effects (Antonelli et al 2006) in several types of mammalian cells. Recently, it has been shown that agonists of PPARg induce apoptosis and exert antiproliferative effects on human papillary carcinoma cells (Ohta et al 2001), prevent distant metastasis of BHP18-21 tumors in nude mice in vivo (Ohta et al 2001), and induce redifferentiation in thyroid cancer cell lines (Klopper et al 2004, Philips et al 2004, Frohlich et al 2005, Park et al 2005, Aiello et al 2006, demonstrating effective therapeutic agents for the treatment of patients with thyroid cancer that fail to respond to traditional treatments (Klopper et al 2004, Philips et al 2004, Frohlich et al 2005, Park et al 2005. Moreover, the expression of PPARg gene and protein were examined in five human anaplastic cancer cell lines (Hayashi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(14), that elicit both anti-neoplastic (14) and antiinflammatory effects (15) in several types of mammalian cells. Recently, it has been shown that TZD exert anti-proliferative effects on human papillary carcinoma cells (16), and it has been proposed that PPARg agonists may be effective for the treatment of patients with thyroid cancer that fails to respond to traditional treatments (17)(18)(19)(20). Moreover, it has been shown that TZD inhibited cell proliferation and down-regulated the invasive potential in five continuous human anaplastic cancer cell lines (21).…”
Section: Introductionmentioning
confidence: 99%
“…PPARg was believed to act as a tumor suppressor in tumors of prostate, breast and colon by inducing apoptosis (Koeffler 2003, Philips et al 2004, Kim et al 2007). Yet TR4's roles in PCa progression can be either as an enhancer of PCa metastasis or as an suppressor of PCa development.…”
Section: Cancermentioning
confidence: 99%
“…PPARg-mediated apoptosis and cell differentiation have been found to be beneficial in the chemotherapy of different types of cancers including prostate, breast, and colon (Koeffler 2003, Philips et al 2004, Kim et al 2007. Moderate anticancer activities of PPARg ligands with minimal toxicities have been observed in patients with liposarcomas and PCa, possibly due to decreased expression of cyclin D1 and increased expression of p21waf1 (Wang et al 2001, Lyles et al 2009).…”
Section: Cancermentioning
confidence: 99%